A Relationship ENT Complaints with Severity and Length of Hospitalization of COVID-19 patients at UMM Hospital - Nimim Putri Zahara; Rahma Rindradi (Universitas Muhammadiyah Malang, 2023)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2 ). Most COVID-19 patients have no symptoms, but if they have complaints or symptoms that are most often felt are fever, cough, anorexia, muscle pain, difficulty of breathing, malaise. Complaints of hyposmia and dysgeusia are early complaints found in COVID-19 patients, which can appear in the first 5-7 days. This can be used to help early detection of COVID-19 cases so that it can break the chain of transmission of COVID-19. This study is an analytic descriptive study. This research was conducted from April to June 2021, in the COVID-19 inpatient room at UMM Hospital. Data analysis in this study used Chi square. All respondents in this study complained coughing, namely 90 respondents. Other complaints include rhinitis, anosmia, sore throat, dysgeusia and vertigo. From the results of the analysis between ENT complaints severity of COVID-19 patient, the value of p=0.231 (p>0.05) was obtained and length of hospitalization has p value 0.116 (p>0.05). In this study, it can be concluded that there is no statistically significant relationship between ENT complaints with the severity and length of hospitalization of COVID-19 patients that treated at RSUMM.